Comparison of perennial ryegrass, Lolium perenne L., ploidy and white clover, Trifolium repens L., inclusion for herbage production, utilization and nutritive value. (24th May 2018) - Guy, Clare; Hennessy, Deirdre; Gilliland, Trevor J.; Coughlan, Fergal; McClearn, Bríd; Dineen, Michael; McCarthy, Brian
Abstract: Increasing herbage dry‐matter (DM) production and utilization on‐farm improves efficiency and sustainability. The objective of this study was to investigate the effect of perennial ryegrass, Lolium perenne L., ploidy and white clover, Trifolium repens L., inclusion on herbage DM production and utilization in an intensive animal grazing system, with high nitrogen (N) inputs (250 kg N ha −1 ) and a high stocking rate (2.75 livestock units ha −1 ). The study was a 2 × 2 factorial design, consisting of diploid and tetraploid cultivars sown as grass‐only and grass‐white clover to give four sward treatments (diploid‐only, tetraploid‐only, diploid‐white clover, tetraploid‐white clover). These were evaluated at each grazing occasion (8–10 per year) for 3 years (2014–2016). Tetraploid‐white and grass‐white clover swards had a lower sward density (−9 and −8 kg DM cm −1, respectively) and perennial ryegrass tiller density (−820 and −1, 436 tillers m −2, respectively) leading to lower postgrazing sward heights (−0.15 and −0.41 cm, respectively), and maintained a superior nutritive value when compared with diploid‐only and grass‐only swards respectively. White clover inclusion resulted in higher productivity characterized by increased herbage DM production (+1, 468 kg DM ha −1 ), improved nutritive value and increased utilization across the three grazing seasons. Varying sward composition with perennial ryegrass ploidy led to improved nutritive value and favourable grazing characteristics in tetraploid swards.